Dynamics of 5-DOF aerostatic spindle with time-varying coefficients of air bearing. (1st June 2022) - Shi, Jianghai; Cao, Hongrui; Jin, Xiaoliang
Abstract: Aerostatic bearing spindle has been widely used in precision machining processes. This paper presents a time-varying dynamic model of aerostatic spindle due to the change of air film thickness under periodic excitation forces. The effects of the magnitude and frequency of the forces on the dynamic coefficients of air bearing and cutting tool deflection are determined quantitatively. The dynamic properties in both translational and rotational directions are considered. The predicted tool vibration with and without considering the time-varying dynamics are compared. Experiments are conducted to measure the cutting tool displacements under stationary and rotational conditions. It is concluded that the variation of the dynamic coefficients plays a significant role in the spindle dynamics when the force magnitude increases beyond a critical value. The effect of unbalance mass on the spindle vibration is investigated based on the proposed model. The results provide guidance in the structure design for the aerostatic spindle and the process planning to improve the dynamic performance of the precision manufacturing process.